Efficacy and Safety of Neostigmine Adjunctive Therapy in Patients With Sepsis or Septic Shock: A Randomized Controlled Trial - El-Tamalawy, Mona M.; Soliman, Moetaza M.; Omara, Amany F.; Rashad, Amal; Ibrahim, Osama M.; El-Shishtawy, Mamdouh M. (Frontiers in Pharmacology, 2022)
Background: Neostigmine has been found to improve survival in animal models of sepsis. However, its feasibility, efficacy, and safety in patients with sepsis or septic shock have not been investigated. Aim: This parallel randomized controlled double-blinded design aimed to investigate the efficacy and safety of neostigmine as an adjunctive therapy in patients with sepsis or septic shock. Patients and Methods: A total of 167 adult patients with sepsis or septic shock were assessed for eligibility; 50 patients were randomized to receive a continuous infusion of neostigmine (0.2 mg/h for 120 h; neostigmine arm) or 0.9% saline (control arm) in addition to standard therapy. The primary outcome was the change in Sequential Organ Failure Assessment (SOFA) scores 120 h after therapy initiation. Secondary outcomes included mortality rates and changes in procalcitonin level. Results: The median (interquartile range) change in SOFA scores improved significantly in the neostigmine arm [−2 (−5, 1)] as compared with the control arm [1.5 (0, 2.8); p = 0.007]. Progression from sepsis to septic shock was more frequent in the control arm (p = 0.01). The incidence of shock reversal in patients with septic shock was significantly lower in the control arm than in the neostigmine arm (p = 0.04). Differences in 28-days mortality rates did not reach statistical significance between the control and neostigmine arms (p = 0.36). Percentage change in procalcitonin levels was similar in both arms (p = 0.74). Conclusion: Neostigmine adjunctive therapy may be safe and effective when administered in patients with sepsis or septic shock. Clinical Trial Registration: NCT04130230.